Increasing Understanding of Research and Development in the University of North Sumatra Student Organization - Nasution, Faiz Albar; Indah Indainanto, Yofiendi; Fahreza, Imam (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The low level of scientific publications in the academic environment is inseparable from limited interests and skills. Efforts are needed to strengthen insight, methodological knowledge, and skills. Students as an integral part in the development of knowledge, are expected to have high interest and motivation in conducting research. So far, the research produced by students has not shown a significant trend. Various causes of problems arise, starting from limitations in formulating ideas, preparing proposals, submitting proposals, determining publications and motivating students to carry out research. It is important for students who are members of the commissariat of the Islamic Student Association of the Faculty of Social and Political Sciences of the University of North Sumatra to be given training in strengthening research knowledge and training in organizational development. The objectives of the training activities include; First, strengthening research insights and assisting in strengthening research problems. Second, training on how to prepare research proposals. Third, assistance and guidance in finding trusted sources of publications. Overall, this training was carried out using participatory techniques, participants were actively involved in all stages of training activities. The output of the service recommends that the participants of the activity carry out various research trainings, in order to improve their abilities, and maintain a high motivational rhythm from students in conducting research. Furthermore, coaching and mentoring for the greatest students in student organizations must be carried out on an ongoing basis.